Impact of Oil Prices on BIST City Indices: Regional Differences in Company Performance - Emre Bulut (Trends in Business and Economics)
This article examines the impact of WTI crude oil prices on nine city indices traded on the BIST, using daily data from 2014 to 2024. The study employs unit root tests, cointegration analysis, and FMOLS estimation to investigate the long-term relationship between oil prices and city indices. The results indicate that oil prices and city indices exhibit a symmetrical and significant relationship in the long run, with different degrees of impact across city indices. The XSANT Index, comprising companies in and around Antalya province, is the most influenced by crude oil prices, whereas the XSIST Index, comprising companies in Istanbul province, is the least affected. The findings have important implications for investors and policymakers who need to monitor oil price fluctuations and their effects on financial market indices.